ANALYSIS OF THE CURRENT SITUATION IN THE FIELD OF HOUSING CONSTRUCTION - E. Astakhova; S. Kalyugina; G. Bobov (Вестник Северо-Кавказского федерального университета, 2022)
The article presents an analysis ofthe current state of the housing construction sector. The indicators that characterize the structure of the housing stock, the commissioning ofresidential buildings. The analysis of the rating of the federal districts, as well as the regions of Russia in terms of housing construction activity, housing affordability, and price level is carried out, and the leading and outsider regions are indicated. The global trend of the problem under consideration is presented, the most active participants of the construction market are indicated. The general problems of the sphere of housing construction, as well as possible directions of their solution at the state level, are identified.